GrADyS-SIM - A OMNET++/INET simulation framework for Internet of Flying things - Lamenza, Thiago; Paulon, Marcelo; Perricone, Breno; Olivieri, Bruno; Endler, Markus (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2022)
This paper describes GrADyS-SIM, a framework for simulating cooperating swarms of UAVs in a joint mission in a hypothetical landscape and communicating through RF radios. The framework was created to aid and verify the communication, coordination, and context-awareness protocols being developed in the GrADyS project. GrADyS-SIM uses the OMNeT++ simulation library and its INET model suite and allows for the addition of modified/customized versions of some simulated components, network configurations, and vehicle coordination to develop new coordination protocols and tested through the framework. The framework simulates UAV movement dictated by a file containing some MAVLink instructions and affected on the fly by different network situations. The UAV swarm’s coordination protocol emerges from individual interactions between UAVs and aims to optimize the collection of sensor data over an area. It also allows simulation of some types of failures to test the protocol’s adaptability. Every node in the simulation is highly configurable, making testing different network topographies, coordination protocols, node hardware configurations, and more a quick task.